ITAF 45 is a pervasive trans -acting factor for picornavirus Type II IRES elements - Michael A. Bellucci; Mehdi Amiri; Stephen Berryman; Andia Moshari; Collins Oduor Owino; Rutger D. Luteijn; Tobias J. Tuthill; Yuri Svitkin; Graham J. Belsham; Frank J. M. van Kuppeveld; Nahum Sonenberg (Proceedings of the National Academy of Sciences, 2025)
Viruses have evolved elaborate mechanisms to hijack the host mRNA translation machinery to direct viral protein synthesis. Picornaviruses, whose RNA genome lacks a cap structure, inhibit cap-dependent mRNA translation, and utilize an internal ribosome entry site (IRES) in the RNA 5′ untranslated region to recruit the 40S ribosomal subunit. IRES activity is stimulated by a set of host proteins termed IRES trans -acting factors (ITAFs). The cellular protein ITAF 45 (also known as PA2G4 or EBP1) was documented as an essential ITAF for foot-and-mouth disease virus (FMDV), with no apparent role in cell-free systems for encephalomyocarditis virus (EMCV) and Theiler’s murine encephalomyelitis virus (TMEV), which are closely related viruses harboring similar IRES elements. Here, we demonstrate that ITAF 45 is a pervasive host factor for picornaviruses containing a Type II IRES. CRISPR/Cas9 knockout of ITAF 45 in several human cell lines conferred resistance to infection with FMDV, EMCV, TMEV, and equine rhinitis A virus (ERAV). We show that ITAF 45 enhances initiation of translation on Type II IRESs in cell line models. This is mediated by the C-terminal lysine-rich region of ITAF 45 known to enable binding to viral RNA. These findings challenge previous reports of a restricted role for ITAF 45 in FMDV infection, thus positioning ITAF 45 as a potential antiviral target for various animal viruses and emerging human cardioviruses.